THE IMPORTANCE OF FLORA ADMINISTRATION IN THE MUNICIPALITY OF GUARUJÁ (SP), BRAZIL - Fernandes, Sidney; Oliveira, Luiz Cláudio Souza de (International Journal of Research -GRANTHAALAYAH, 2021)
Objective – The study aimed to map, identify and catalog the tree species present in the municipality of Guarujá, Metropolitan Region of Baixada Santista, State of São Paulo, used in the afforestation of the municipality. The criteria for the choice of species by the city were evaluated, aiming through this survey, future proposals for better management in the administration of inclusion of urban flora; inclusion of native species, prioritizing species that are attractive to the region's fauna. Methods - During the study, samples were taken in 5 (five) points of the city of Guarujá, with materials that present an equivalent representation of populations. The studies were carried out following seasonality, in order to observe the environmental influence on the distribution of plants. Results - Twelve families, 28 genera and 29 species were identified in the samples carried out in 117 streets in 5 districts, being 57 streets in the Vila Áurea district, 24 streets in the Jardim Progresso district, 10 streets in the Santa Rosa district, 12 streets in the Pitangueiras district and 10 streets in the Virginia Garden District. Conclusion - The interest in paying attention to plant species used in afforestation in the municipality of Guarujá is due to the fact that inappropriate afforestation is observed, sometimes planted by residents, without guidance and thus without technical criteria, thus creating a future problem, for example, causing problems urban areas such as pavement destruction, changes in the landscape and species that are not always attractive to fauna. Another fact that is also observed is the low diversity of species present, many of them exotic and not native to the region.